Technology to advance infectious disease forecasting for outbreak management - Dylan B. George (Nature Portfolio, 2019)
Forecasting is beginning to be integrated into decision-making processes for infectious disease outbreak response. We discuss how technologies could accelerate the adoption of forecasting among public health practitioners, improve epidemic management, save lives, and reduce the economic impact of outbreaks.